Procedure Text To Evacuation Simulation: Effectiveness Of Interactive Media Based On Ai Conversation In Indonesian Language Learning For Post-Earthquake Crisis Communication - Ilhami Desrina (International journal of technology and education research, 2026)
Learning text procedure in curriculum Indonesian still​ dominated approach conventional which is static, so that participant educate No own experience simulation communication realistic crisis​ For face situation evacuation post- earthquake research This aim For analyze effectiveness of interactive media conversational AI- based in increase understanding structure and rules text procedures, training verbal and nonverbal responses, comparing them with conventional media, as well as identify obstacles and support implementation. The type of research used is studies library with data sources in the form of books, articles journal scientific, and reports results research analyzed​ use technique analysis content. Research results show that scenario evacuation interactive conversational AI- based in a way significant increase understanding structure and rules text procedure through experience dynamic and contextual learning. Conversational AI proven effective in practice verbal response in the form of speed taking decision linguistic and nonverbal responses in the form of ability read signal emotional victim. Comparison with conventional media show the advantages of AI media in matter authenticity simulation, frequency practice, retention skills and confidence self students. Implementation constraints covering latency technical, limitations infrastructure, mismatch context local, and potential retraumatization, however supported by the availability of modern AI models, support policies, as well as training source Power human. Research This conclude that interactive media conversational AI- based effective For learning text procedure evacuation and ready implemented in a way gradually with adjustment context local as well as mentoring psychological.